Internalization of Multicultural Values in Islamic Boarding School-Based Education: An Empirical Study at the Amanatul Ummah Islamic Boarding School in Pacet, Mojokerto - Mohammad Rozi Indrafuddin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This article reveals the process of internalizing multicultural values in Islamic boarding school, with a focus on the Amanatul Ummah Pacet Islamic Boarding School in Pacet Mojokerto. In the pluralistic social context of Indonesia, Islamic boarding schools have a strategic role that not only transmits religious knowledge but also shapes the character of students to be tolerant, humanistic, and nationally oriented. This study uses a qualitative approach with a case study design. Data were obtained through participatory observation, in-depth interviews, and documentation, then analyzed using Miles and Huberman's interactive model. The results show that the internalization of multicultural values in pesantren is carried out through three main stages: (1) value transformation, (2) value transaction, and (3) value transinternalization. The first stage takes place through formal learning activities in the classroom, the second stage through social interaction in the pesantren dormitory environment, and the third stage through the example set by caregivers and teachers (uswah hasanah). The main values internalized include tolerance, honesty, equality, democracy, and nationalism. The internalization of Islamic-based multicultural values produces santri with moderate, open characters and a strong sense of social and national awareness. This study concludes that the Amanatul Ummah Islamic Boarding School is a model of Islamic education that successfully harmonizes Islamic, national, and humanitarian values through a continuous and contextual process of multicultural value internalization.